The Influence of Behavior of Students of SMP Negeri 1 Sirenja, Donggala Regency on Perceptions of Danger of Drugs - Rony Gunawan; Munir Salham; Sriwahyudin Moonti (Journal of Public Health and Pharmacy)
Drugs are drugs used for medical purposes. Its use is based on a doctor's prescription and under government supervision. Drug use without a doctor's prescription can cause dependence and health problems. This study aims to determine the effect of student behavior in SMP Negeri 1 Sirenja, Donggala Regency, on the Perception of the Danger of Drugs. This type of research is an analytical survey method using a cross sectional approach. Determination of the sample in this study was done by random sampling. Samples were taken as many as 35 people and using Chi-square test data analysis. The results of this study indicate that there is an influence of students' knowledge with the perception of the dangers of drugs as evidenced by statistical tests with p value = 0.028 < 0.05, there is an influence of students' attitudes with perceptions of the dangers of drugs as evidenced by statistical tests with p value = 0.044 < 0.05 and there is no effect of students' actions with the perception of the dangers of drugs as evidenced by statistical tests with p = 0.328 > 0.05. This study suggests to always provide information related to the dangers of drugs to students through socialization or counseling so that students better understand and understand the dangers of drugs to reduce the risk of drug abuse.